Concur–processes of wear and renewal of surfaces of knot of friction. Part I. Theoretical bases of the generalized method of tests on a wear on a fourball-shaped chart - Кузьменко, А.Г. (Problems of Tribology, 2014)
Concur–processes of wear and renewal of surfaces of knot of friction. Part I. Theoretical bases of the generalized method of tests on a wear on a fourball-shaped chart